Incorporação e mercado imobiliário: a resolução contratual por inadimplemento do adquirente sob a perspectiva da lei nº 13.786/18 - Beltrão, Rogério Coutinho (2019)
The present research aims to verify the best way to approach the interest of the collective of buyers, the real estate market, and the buyer in default when the purchase and sale agreements termination occurs in real estate Incorporation, in view of the recent proposed legislative amendment Law no. 13.786/18, which, in contrast to the case-law consolidated by Supreme Court of Justice no. 543, attributed the reimbursement to the term and the retention percentages of the amounts paid by the buyer in the distract and termination by up to 25% or 50%, whether or not the constructor has adopted the patrimonial segregation regime. This compatibility is based on the analysis of the institutes set forth in Law no. 4.591/64 in dialogue with Law no. 8.078/90, with a view to the realization of the national economic order, according to the predicates of article 170 of the Federal Constitution, in order to harmonize individual and collective interests, arising from free enterprise, private property, and its social function and consumer protection, considering that the contracts signed by Law no. 4591/64 are irreversible. It is therefore classified as a qualitative methodological research, aiming to draw conclusions about the form of contractual terminated in the real estate development, procedures, form and percentage of retention, based on the deductive method, starting with the general framework highlighted by Jurisprudence and Doctrine, in order to reach the desired conclusions, through a strictly dogmatic approach, with bibliographical revision of national and foreign doctrines, scientific articles, jurisprudence and analysis of statistical data already produced.